Physicochemistry aspects on frictional interfaces - Cai, Meirong; Yu, Qiangliang; Zhou, Feng; Liu, Weimin (Friction, 2017)
Friction exists wherever relative motion occurs and is the main source of energy consumption. Lubrication plays a significant role in improving fuel efficiency, reducing emissions, and prolonging the service life of machines. Surface interactions between two moving solid surfaces or the flow of a fluid (and/or environment) on a solid surface are the primary causes of friction. Apart from the mechanical design of moving parts, surface physicochemistry is of crucial importance to lubrication. This review deals with the frontier research on controlling friction and lubrication, highlights the importance of physicochemistry aspects, and enumerates the state-of-the-art chemistry solutions to tribological issues. It aims at inspiring talented young scientists from different fields to make significant contributions to the area.